The complementary formulary : - Lessell, Colin B. (Butterworth Heinemann, 2001)
This book has been especial written for the professional prescriber pharmacist. Rather than being an unpractical, complex and voluminous textbook of complementary therapies, it is highly selesct and pointed extraction from personal experience, current practice and literature.